Talent Guidance Assistance in Junior High School Basketball Extracurriculars in Sukoharjo Regency - Waluyo; Baskoro Nugroho Putro; Hanik Liskustyawati; Tri Aprilijanto Utomo; Agus Mukholid; Ahmad Septiandika Adirahma (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
Talent scouting is part of the achievement development process. Basketball is an extracurricular activity owned by almost every junior high school. Sukoharjo Regency is one of the districts with basketball coaching conditions that depend on extracurricular coaching. The management of basketball extracurricular activities is not as good as that of a club or academy. Schools are generally only able to employ one coach for extracurricular basketball. The coach is responsible for simultaneously fostering the achievements of the men's and women's teams. Coaching is a heavy responsibility because the treatment of extracurricular activities between boys and girls must be different. Support for facilities and infrastructure is also a problem because most schools have multifunctional fields that must be used interchangeably. Student participation in basketball extracurricular activities occurs voluntarily. That participation process proves there is no scientific selection process in recruiting participants for basketball extracurricular activities. Sport-themed extracurricular activities pay close attention to anthropometry and physical condition readiness. Coaches for basketball extracurricular activities need help to facilitate the coaching process. Talent scouting can be used as an alternative to facilitate the process of fostering extracurricular activities. Talent scouting can be used as a form of selection for students who want to join or as an instrument to determine the condition of students who have joined extracurricular activities. Assistance to basketball extracurricular trainers is carried out directly by employing "FKOR UNS Goes to School". Trainers will be given a theoretical explanation and invited to be directly involved in the test and measurement process.